Restorasi Endocrown Gigi Molar Pertama Rahang Atas Pasca Perawatan Endodontik (Laporan Kasus) - Rosita Stefani (Fakultas Kedokteran Gigi Universitas Trisakti, 2019)
Background: Restoration after endodontic treatment is still a challenge that must be performed by doctors in daily practice. The gold standard treatment for this case is post-core crown. However, this aggressive preparation for post-core crown does not in line with the minimally invasive concept in modern dentistry. Objective: To restore the function and aesthetic of maxillary first molars after endodontic treatment using Endocrown. Case: A 54-year-old male patient came to the clinic with a broken amalgam restoration on the first right upper molar since 3 months ago. The restoration was felt sharp thus iritate the tongue. On clinical and radiographic examination, an old amalgam restoration was seen on the occlusal surface and had reached the pulp. At the first visit, one visit endodontic was done with warm vertical condensation technique. Gutta-percha masterpoint was cut until ⅓ apical was filled and at ⅓ middle and ⅓ coronal the root canal was filled with injectable thermoplastized gutta-percha which is compacted until 2 mm below the orifice. On the next visit, gutta percha was cut as much as 2 mm and filled with core material as intraradicular retention as deep as 4 mm. Preparation is made by the butt-joint equigingival margin around the surface with a retention cavity in the middle of the pulp chamber. After the completion of tooth preparation, the impression was made with polyvinyl siloxane silicone. At the third visit, endocrown was tested to check the marginal fit and accuracy, then cemented using resin cement, and checked using radiography. Conclusion: Endocrown can serve as an alternative restoration which is conservative, have good aesthetic, functional, and minimally invasive.